Parthenolide Blocks Cocaine’s Effect on Spontaneous Firing Activity of Dopaminergic Neurons in the Ventral Tegmental Area - Schwarz, David (Bentham Science Publishers Ltd, 2011)
Chronic cocaine administration leads to catecholamine reuptake inhibition which enhances reward and motivational behaviors. Ventral Tegmental Area dopaminergic (VTA DA) neuronal firing is associated with changes in reward predictive signals. Acute cocaine injections inhibit putative VTA DA cell firing in vertebrates. Parthenolide, a compound isolated from the feverfew plant (Tanacetum parthenium), has been shown to substantially inhibit cocaine’s locomotion effects in a planarian animal model (Pagán et al., 2008). Here we investigated the effects of parthenolide on the spontaneous firing activity of putative VTA DA neurons in anesthetized male rats (250-300g). Single-unit recordings were analyzed after intravenous (i.v.) parthenolide administration followed by 1mg/kg i.v. cocaine injection. Results showed that parthenolide at 0.125 mg/kg and 0.250mg/kg significantly blocked cocaine’s inhibitory effect on DA neuronal firing rate and bursting activity (p< 0.05, two way ANOVA). We propose that parthenolide might inhibit cocaine’s effects on VTA DA neurons via its interaction with a common binding site at monoamine transporters. It is suggested that parthenolide could have a potential use as an overdose antidote or therapeutic agent to cocaine intoxication.